Geochemical research of soil and attic dust in Litija area, Slovenia - Mateja Jemec; Rober Šajn (Geologija, 2007)
Geochemical research was carried as part of the environmental research project at the Geological Survey of Slovenia. The aim of the project was to determine the impact on the environment caused by heavy metals released in the environment during mining and smeltingactivity in the area of Litija. The samples of attic dust and soil (0–5 cm) were examined with the view to separate the natural distribution of chemical elements in the environment from the one caused by past mining and smelting activities. Based on chemically analyses we determine two main geochemical associations and their spatial distribution. First geochemical association (Al, Co, Ce, K, La, Li, Nb, Rb, Sc, Ta, Th in Ti) is influencedmainlybynatural source, the second man-made association (As, Cd, Hg, Pb, Sb, Sn in Zn) is caused mainly because of mining and lead smelting.